STEM CELL RESEARCH DEVELOPMENT AND ITS PROTECTION IN INDONESIA - Tomi Suryo Utomo (Fakultas Hukum Universitas Gadjah Mada, 2012)
This research discusses the possibility of patenting stem cells under the Indonesian patent law by focusing on two essential issues: (a) what approaches should be chosen by the Indonesian government to protect stem cell research under the Indonesian Patent Act and non-patent regulations? and (b) what types of stem cells can be protected under the Indonesian Patent Act? In order to provide comparative perspectives, this paper discusses the experience and policies of the US, German and South Korean governments in protecting stem cell research under their patent acts. Penelitian ini mendiskusikan kemungkinan mematenkan sel punca dalam hukum paten di Indonesia dengan memfokuskan pada dua isu pokok: (a) Pendekatan apa yang sebaiknya dipilih oleh pemerintahan Indonesia untuk melindungi penelitian sel punca dalam hukum paten Indonesia dan peraturan non paten? (b) Tipe sel punca apa yang dapat dilindungi dalam hukum paten Indonesia? Untuk mencakupi pendekatan melalui perbandingan dengan luar negeri, penelitian ini membahas pengalaman dan kebijakan di pemerintahan AS, Jerman, dan Korea Selatan dalam melindungi penelitan sel punca dalam hukum paten masing-masing negara.